Meningkatkan Kesadaran Masyarakat di Era New Normal untuk Menggunakan Masker dan Cuci Tangan dengan Sabun di Pasar Sayur Desa Rejosari Kecamatan Bantur Kabupaten Malang - RM Mahrus Alie; Suryaman Suryaman; Windi Ayu Lestari (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2022)
The covid- 19 pandemic that has swept across the globe including Indonesia is now a serious problem and must be given immediate solutions in a normal new age society immediate solutions in a normal new age society would have been much more protective by applying the physical of chisels or by continuing the health protocols promoted by governments as well as by building a return to the habit of washing hands and wearing masks. One of the vegetable markets in the repay village of Bantur district is one of the many places through which communities will have a high risk of growing the virus. The objective of this enhancement is the distribution of masks and the use of hand sanitiums to revive the community community to maintain health protocol. Wearing masks and hand washing with soap diligently is one way to prevent the spread of virus in the saffron village’s saffron, the reflexively germination of research using a qualitative method with an approach to literature. Data analysis using the decryption. The source of the data used are articles, journals, and official documents, from research found that in the face of the covid pandemic- 19 this society is located in the veggie market of the Bantur district